Analysis of Satisfaction Factor for Development Recommendation Tourism Web System - Sfenrianto, Suroso J.S.; GIRSANG, Abba Suganda; RUMAN, Fikri (Journal of Environmental Management and Tourism; Vol 7 No 1 (2016): JEMT Volume VII, Issue 1(13) Spring 2016, 2016)
Indoensia.travel as one tourism web which is managed Indonesia government should give a satisfaction for users to provide useful information and travel referenced in Indonesia. However, many users have expressed dissatisfaction such as system has not provided sightseeing recommendations in accordance with the wishes and needs of users. Therefore, this paper aims to conduct the gap analysis based on some dimensions in Indonesia.travel. Analyzed is performed between user expectation and the existing web system to obtain the gap point. ISO 9126 which is issued by the International Organization for Standardization (ISO) and International Electrotechnical Commission (IEC) is used for standard to obtain the gap point. The gap point on functionality, usability and efficiency dimension are used to measure the gap. This significant gap obtained is used to develop the recommendation system in order to enhance the satisfaction user.
Keywords: Indonesia travel; ISO; tourism; analysis gap; recommendation